Presentation of Financial Assets in the Monetary Statistics - V. N. Salin; O. Y. Sitnikova; L. Y. Arhangelskaya (Статистика и экономика, 2022)
The purpose of the study. Currently, the issues of determining, presenting and analyzing indicators of economic assets, in particular, financial ones, are relevant, since financial assets, along with nonfinancial ones, constitute the most important characteristic of national wealth as a level of development of the country and are the basis for constructing national accounts, indicators of monetary statistics and other sections of macroeconomic statistics. In modern conditions, the role of these constructions in making effective management decisions at the macro level, individual sectors, economic entities, on the development of the national economy as a whole is increasing. The aim of the work is to systematize theoretical and practical developments on the definition and presentation of data on financial assets in modern monetary statistics of Russia, to identify areas for improving methods for assessing financial assets, a system of indicators characterizing their presence, structure and dynamics.Materials and methods. In the paper, the authors considered the essence, functions, classifications of financial assets and liabilities, applied structural and dynamic data analysis, as well as methods of theoretical research in the form of generalization, comparison and special analytical procedures based on official statistics from Rosstat, the Bank of Russia, the Ministry of Finance and international statistical organizations.Results. The work formulates the main directions of the study of financial assets, based on modern international statistical standards, taking into account domestic practice. Topical issues of the theory and practice of statistical collection and presentation of data on financial assets in monetary statistics, the application of definitions and classifications of international standards to Russian official statistics are considered. The features of the reflection of data on financial assets at the macro level, in the system of indicators of monetary statistics, have been formulated. The authors carried out a quantitative assessment of the structure and dynamics of indicators of monetary statistics in Russia, which characterize the state and movement of financial assets and liabilities.Conclusion. A statistical study of transactions with financial assets and in connection with the formation of monetary aggregates makes it possible to identify not only the main trends in the development of these processes, but also makes it possible to characterize the contribution of a particular subsector to the total value of financial intermediation, to analyze the relationship between the financial corporations’ sector and other sectors, and also a comprehensive change in the volume and composition of stocks and flows of financial assets as a result of exchanges between residents and non-residents.The authors comprehensively reviewed the methodological framework for constructing money aggregates and reviews of the financial corporations’ sector, incl. in the context of financial instruments. Statistical information on financial assets in monetary statistics is presented in terms of the formation of the money supply, other aggregates, the base, as well as the interaction between the institutional subsectors of the financial sector. A comprehensive description of the presence and movement of financial assets in the composition of monetary statistics can be obtained from the monetary surveys, containing data on the flows and stocks of financial assets and liabilities of financial corporations (residents) in relation to all other sectors (residents), as well as non-residents.All considered data are comparable [17,18] since basically, one classification of financial instruments is applied, a different degree of detail can be applied in practice for different constructions, but the base is the same. Questions of the theory and practice of presenting indicators of financial assets in the considered sections of macrostatistics and their analysis are a relevant and promising direction for improving national statistical accounting. Work in this direction continues, and the process of actively introducing international standards into domestic statistics has been going on for quite a long time. In addition, telecommuting, collecting information via the Internet, the emergence of a large number of new financial instruments and transactions, including modified ones, in the business turnover of institutional units complicate their identification and classification.The authors of the presented study have previously considered in their articles the problems of macroeconomic calculations, which allowed them in their work to consider in more detail the topical issues related to the processes of reflection of financial assets in monetary statistics.